Protective effect of Genistein against N-nitrosodiethylamine (NDEA)-induced hepatotoxicity in Swiss albino rats - Fahad Ali; Rahul; Falaq Naz; Smita Jyoti; Yasir Hasan Siddique (Elsevier, 2015)
In the present study, we studied the effect of Genistein against the hepatotoxicity induced by N-nitrosodiethylamine (NDEA). NDEA is present in almost all kinds of food stuff and has been reported to be a hepatocarcinogen. The male rats were exposed to NDEA (0.1 mg/mL) dissolved in drinking water separately and along with 25, 50, 100 mg/mL of Genistein for 21 days. The activities of serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT), alkaline phosphatase (ALP) and lactate dehydrogenase (LDH) were measured in blood serum. Lipid peroxidation, protein carbonyl content, micronucleus frequency and DNA damage (Comet assay) were performed on rat hepatocytes. The results of the study reveal that the treatment of NDEA along with Genistein showed a significant dose-dependent decrease in the levels of blood serum enzymes i.e., SGOT, SGPT, ALP and LDH (P<0.05). The HE staining of histological sections of the liver also revealed a protective effect of Genistein. A significant dose-dependent reduction in the lipid peroxidation and protein carbonyl content was observed in rats exposed to NDEA (0.1 mg/mL) along with Genistein (P<0.05). The results obtained for the comet assay in rat hepatocytes showed a significant dose-dependent decrease in the mean tail length (P<0.05). Thus the present study supports the hepatoprotective role of Genistein. Keywords: Genistein, N-nitrosodiethylamine, Serum enzymes, Antigenotoxic, Hepatoprotective